Health information seeking behavior through the internet in the community - Hazhar, Tsabita Vania; Setiawan, Asty Samiaty; Suryanti, Netty (Padjadjaran Journal of Dental Researchers and Students, 2023)
ABSTRACTIntroduction: Teledentistry is a method of dental and oral health services used during the COVID-19 pandemic. Telemedicine during the 2019 Corona Virus Disease (COVID-19) Pandemic in Indonesia, dentists can choose two options in practicing during the COVID-19 pandemic..The purpose of this study is to determine dentists’ perception of the use of teledentistry in dental practice during the COVID-19 pandemic in Greater Bandung area. Methods: This cross-sectional descriptive study used an online questionnaire containing 23 Likert-type questions to determine dentists’ perception of concerns related to data security, the ability of teledentistry to improve practice, the usefulness of teledentistry in dental practice, and the usefulness of teledentistry for patients. Results: A total of 105 respondents were obtained and 103 respondents who met the criteria. More than 80% of respondents strongly agree or agree that teledentistry can help shorten patient waiting lists, help avoid unnecessary hospital visits, help monitoring patient conditions, improve communication with patients, and increase patient satisfaction. The potential of digital data/information forgery has the highest level of concern with a response of very concern and little concern as much as 60,2%. Conclusion: Majority of dentists in Greater Bandung area showed a positive response to the ability of the teledentistry system to improve practice, the usefulness of the teledentistry system in practice, and the usefulness of the teledentistry system for patients. The things that raised doubts about the use of teledentistry system are related to security and confidentiality issues and less accurate and adequate diagnosis.KEY WORDS: Teledentistry, dentist, perception, COVID 19, pandemicPerilaku pencarian informasi kesehatan melalui internet pada masyarakatABSTRAKPendahuluan: Teledentistry merupakan metode pelayanan kesehatan gigi dan mulut yang digunakan selama masa pandemi COVID-19. Telemedicine pada masa Pandemi Corona Virus Disease 2019 (COVID-19) di Indonesia, dokter gigi dapat memilih dua pilihan dalam pelaksanaan praktik selama pandemi COVID-19. Tujuan penelitian mengetahui persepsi dokter gigi mengenai penggunaan teledentistry dalam praktik selama masa pandemi COVID-19. Metode: Penelitian deskriptif cross-sectional menggunakan kuesioner secara daring yang berisi 23 pertanyaan tipe-Likert untuk mengetahui persepsi dokter gigi terhadap kekhawatiran yang berkaitan dengan keamanan data, kemampuan teledentistry untuk meningkatkan praktik, kegunaan teledentistry dalam praktik kedokteran gigi, dan kegunaan teledentistry untuk pasien. Hasil: Sebanyak 105 responden didapatkan dan 103 responden yang memenuhi kriteria. Lebih dari 80% responden sangat setuju dan setuju teledentistry dapat membantu mempersingkat daftar tunggu pasien, membantu menghindari kunjungan ke rumah sakit yang tidak diperlukan, membantu pemantauan kondisi pasien, meningkatkan komunikasi dengan pasien, dan meningkatkan kepuasan pasien. Potensi pemalsuan data/informasi digital memiliki tingkat kekhawatiran tertinggi dengan respon sangat khawatir dan sedikit khawatir sebanyak 60,2%. Simpulan: Mayoritas dokter gigi menunjukkan respon positif terhadap kemampuan sistem teledentistry dalam meningkatkan praktik pelayanan, kegunaan sistem teledentistry dalam praktik pelayanan kedokteran gigi, dan kegunaan sistem teledentistry pada pasien. Hal yang menimbulkan keraguan dalam penggunaan sistem teledentistry berkaitan dengan masalah keamanan dan kerahasiaan, serta diagnosis yang kurang akurat dan memadai.KATA KUNCI: Teledentistry, dokter gigi, persepsi, COVID 19, pandemi